2010
DOI: 10.1007/s00417-010-1464-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical impurities and contaminants in different silicone oils in human eyes before and after prolonged use

Abstract: As cholesterol concentrations increased and LMWC D4 decreased similarly in both SiO brands, their stability might be regarded as equal. The smallest LMWC molecules (D4) appear to have the greatest capability to diffuse into the surrounding ocular tissues. The low grade of emulsification (12.9 %) in our patients could not be related to LMWC or cholesterol changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Nakamura et al11 found that the concentration of LMWC up to D6 changed in SilOil recovered from human and rabbit eyes, with a significantly decline of D4, whereas the concentrations of heavier siloxanes remained stable. Significant time-dependent decrease in D4 concentration also has been detected recently in two different 5000 mPa·s SilOil 16. Based on these data, LMWC has been suggested to diffuse into surrounding ocular tissue.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Nakamura et al11 found that the concentration of LMWC up to D6 changed in SilOil recovered from human and rabbit eyes, with a significantly decline of D4, whereas the concentrations of heavier siloxanes remained stable. Significant time-dependent decrease in D4 concentration also has been detected recently in two different 5000 mPa·s SilOil 16. Based on these data, LMWC has been suggested to diffuse into surrounding ocular tissue.…”
Section: Discussionmentioning
confidence: 55%
“…The surfactants can be divided in two groups of molecules: biosurfactants (HDL-apolipoproteins, plasma lipoproteins, red blood cell membranes, growth factors, and cytokines) and SilOil impurities 2. Low molecular weight components with M ≤ 1000 g/mol are considered significant chemical impurities of SilOil 16. These compounds are able to lower the IT of SilOil and, consequently, generate emulsification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the high surface tension, in practice silicone oils undergo emulsification, which can lead to several complications including cataract, keratopathy, glaucoma and silicone retinopathy [13]. Silicone oils have excellent chemical stability, but many studies proved that they are not inert biologically, some impurities such as retinol [14], lowmolecular-weight components (LMWC) [4], residual catalysts [15], OH-endgroups [16], and cholesterol [17] were detected in silicone oils, which can probably improve emulsification due…”
Section: Discussionmentioning
confidence: 99%